Contribution of Double Legs Speed Hops and Pull Down Resistance Bands Training to the 50 Meter Breaststroke Swimming Speed of Male K.U II Athletes at the Medan Aquatic Swimming Club in 2023 - Rodcin Mard Sinurat; Imran Akhmad (Journal of Indonesian Active in Sports, 2024)
This research is an experimental study whose aim is to determine the contribution of Double Legs Speed Hops and Pull Down Resistance Bands training to the 50 Meter Breaststroke Swimming Speed of Male K.U II Athletes at the Medan Aquatic Swimming Club in 2023. The population of swimming athletes at the Aquatic Swimming Club totaling 20 people, using purposive sampling technique a sample of 8 people was obtained. The research was conducted for 6 weeks, 18 meetings and 3 times a week. Before testing the hypothesis, a prerequisite Normality test was carried out using the Lilifors test so that the three variables were normal and the Homogeneity test (F test) then the three variables after testing the data were homogeneous. Hypothesis analysis produces Fcount = 7.259 and Ftable = 5.79 so that Fcount > Ftable so after testing it can be concluded that there is a significant contribution from Double Legs Speed Hops and Pull Down Resistance Bands training to 50 Breaststroke Swimming Speed K.U II Male Athlete Meter at Aquatic Swimming Club Medan in 2023.